Assessment, Evaluation, and Programming System for Infants and Children: What are Salient Development and Research Factors to Consider? - Macy, Marisa; Chen, Ching-I; Macy, Robert (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Early childhood professionals are increasingly pressed to use evidence-based measures when assessing young children. Professional time and resources to investigate research is limited, and takes time away from the delivery of direct services. The literature review is to describe the progression of a widely used curriculum-based assessment (CBA), the Assessment, Evaluation, and Programming System for Infants and Children (AEPS). In addition to sharing the development of this early childhood measure, we identified 19 studies from the available research found in various databases that have investigated the evidence supporting the use of this measure. Findings have implications for the validity, reliability, and utility of the AEPS.